Partial vs full range of motion resistance training: A systematic review and meta-analysis - Wolf, M.; Androulakis-Korakakis, P.; Fisher, J.; Schoenfeld, B.; Steele, J. (International Journal of Strength and Conditioning, 2023)
Background: Range of motion (ROM) during resistance training is of growing interest and is potentially used to elicit differing adaptations (e.g. muscle hypertrophy and muscular strength and power). To date, attempts at synthesising the data on ROM during resistance training have primarily focused on muscle hypertrophy in the lower body.